Circulating apelin and chemerin levels in patients with polycystic ovary syndrome: A meta-analysis - Gao, Yiming; Xin, Caihong; Fan, Huaying; Sun, Xin; Wang, Hongli (Frontiers in Endocrinology, 2023)
Background Polycystic ovary syndrome (PCOS) is one of the most common gynecological endocrine disorders. Apelin and chemerin are newly identified adipokines, which are higher in obesity and diabetes. Studies have found that the serum apelin and chemerin levels in patients with PCOS are significantly increased. However, other studies showed the opposite results. Therefore, the relationship between those two adipokines and PCOS is still controversial. Aim This meta-analysis was conducted to statistically evaluate the apelin and chemerin levels of patients with PCOS. Methods We searched the Web of Science, Embase, PubMed, and Google Scholar databases for potential studies. “Polycystic ovary syndrome” or “PCOS” in combination with the terms “apelin” or “chemerin” were used as keywords search titles or abstracts. The publication period examined was between 1990 and 2021. Standardized mean differences (SMD) with corresponding 95% confidence intervals (CIs) were determined as the results of the meta-analysis. Results A total of 148 articles were initially retrieved, and 18 qualified articles were finally obtained through preliminary screening and quality evaluation. The publications together contain 1,265 cases and 894 controls. The results of the meta-analysis showed that the circulating chemerin levels in patients with PCOS were significantly higher than those in the controls (SMD: 0.79, 95% CI [0.36, 1.23]), and there was no significant difference in circulating apelin between patients with PCOS and controls (SMD: 0.57, 95% CI [-0.21, 1.35]). Conclusions This meta-analysis is the first to evaluate circulating apelin and chemerin levels in patients with PCOS. Our findings suggest that circulating chemerin levels of patients with PCOS are significantly higher than those of healthy controls. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=218316, identifier CRD42020218316.